Rancang Bangun Mesin Pengiris Tempe Otomatis Dengan Pengaturan Ketebalan - Hendriko, Hendriko; Hura, Menti Diana; Jaenudin, Jajang; Rahmawaty, Made; Khamdi, Nur (Politeknik Negeri Sriwijaya, Indonesia, 2022)
Tempe is a traditional Indonesian food that can be processed into various derivative food products, including chips and mendoan. Many MSMEs have developed tempe chip products, but the tempe slicing process is still done manually. The manual process has the disadvantage of taking a long time, requiring operators, and inconsistent results. In this study, an automatic tempe slicing machine was developed. The developed machine uses a control system so that it can adjust the thickness of the slices by manipulating the rotational speed of the driving motor. The mechanical design of the tempe pushing system and hopper causes the process to take place continuously. Tests to determine the performance of the machine in producing tempe slices, and to determine the capacity of the machine have been carried out. The results show that the machine can slice tempe well starting from a thickness of 2 mm. The test results also show that the deviation of the thickness of the slices is not significant, which is between -2.2% - 2.5%. Machine capacity depends on the thickness of the slices. For 3 mm slices, the machine capacity is 22 29 kg/hour. Meanwhile, the machine capacity for slice thickness of 5 mm and 7 mm is 31.85 kg/hour and 38.96 kg/hour, subsequently.